2014
DOI: 10.2478/msr-2014-0002
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Film Thickness Estimation using Electrical Capacitance Tomography

Abstract: In air/oil lubrication systems, the flow parameters, e.g., flow pattern, liquid film thickness, and air/oil flow rate, are of great importance to the transportation efficiency. In most cases, the on-going two-phase flow is annular flow with the oil moving along the tube wall and the air travelling at high speed in the center. This usually results in the formation of a thin oil film, the thickness of which is a key parameter determining the efficiency of the lubrication system. As the oil film thickness of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Liquid film occurs very often in industrial applications with thicknesses that may range from below 10 μm to above 5 mm (Cui et al 2014). Engine tribology has been always an important subject of study in the automotive industry (Macián et al 2016).…”
Section: Biofuels For Diesel Enginesmentioning
confidence: 99%
“…Liquid film occurs very often in industrial applications with thicknesses that may range from below 10 μm to above 5 mm (Cui et al 2014). Engine tribology has been always an important subject of study in the automotive industry (Macián et al 2016).…”
Section: Biofuels For Diesel Enginesmentioning
confidence: 99%
“…The distance between the two sensors was 600 m. Each ECT sensor was powered using a dedicated data acquisition system. The data acquisition systems were field-programmable gate array (FPGA) based and communicated with the host PC via a USB link, with a data acquisition rate of 800 frames per second (fps) (Cui, Wang, Chen, Xu, & Yang, 2011;Cui, Yang, Sun, & Wang, 2014). To avoid possible mutual interference between the two data acquisition systems, through the metal pipeline, different excitation frequencies were assigned to the two systems.…”
Section: Set-up and Instrumentsmentioning
confidence: 99%
“…With the change of the medium’s permittivity from a low value to a high value in the ECT imaging area, the capacitance values among the different electrode pairs behave totally differently in terms of their properties and nonlinearities. Cui et al [ 43 ] and Yang et al [ 44 ] reported and preliminarily analyzed the effect of the nonlinearity of capacitances between different electrode pairs on ECT image reconstruction. This issue may need to be investigated more deeply in future studies on ECT image reconstruction, particularly while the permittivity distribution inside the sensor has a relatively high contrast variation.…”
Section: The Simulation Part Of the Benchmark Datasetmentioning
confidence: 99%